Ethnobotanical survey of poisonous plants and their medicinal uses in Chamba block, district Tehri Garhwal, Uttarakhand, India - Dangwal, Lakhi Ram; Pundir, Manisha; Shukla, Umang Kumar; Rawat, Minakshi (Ecological Questions, 2026)
The current research is based on the documentation of poisonous plants in the Chamba block of Tehri Garhwal district, Uttarakhand, India. Documentation and identification of poisonous plants provide scientifically authentic ethnobotanical information on their perceived toxic potential based on local knowledge and traditional use. It provides valuable insights into the cultural, economic, and ethnomedicinal relevance of these poisonous natural plants across the different communities in the study site. A systematic, intensive ethnobotanical survey was conducted from June 2023 to July 2024 to document the traditional use of poisonous plants by local communities. Many of these poisonous plants are used to treat ailments like diarrhea, diabetes, fever, joint pain, and snake bites, often without awareness of their toxic effects. The study identified 30 poisonous species across 24 genera and 18 families, including 14 dicots, 2 monocots, and 2 gymnosperms. Euphorbiaceae was the most dominant family. Each plant’s scientific and local details, toxic parts, and medicinal uses were recorded. This first regional study highlights the need to raise awareness and preserve traditional knowledge and offers valuable insights for researchers and students.